2015
DOI: 10.1002/pat.3700
|View full text |Cite
|
Sign up to set email alerts
|

Novel propargyl-substituted azo-coupled phenolic resins

Abstract: Novel propargyl that contains phenolic resins via azo-coupling reaction was synthesized. Peculiarities of curing process were investigated by differential scanning calorimetry analysis. Polymerization of resins with azo groups was estimated to be affected by radicals obtained at resin decomposition causing 10°C peak shift to lower temperatures in comparison with resin containing only propargyl group. At the same time, polymerization of triple propargyl bond was shown to not proceed at radical initiation until … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Propargyl ether resin, a new type of high‐temperature‐resistant thermosetting resin developed in recent years, is a material with many potential advantages, including its good processability, long‐term storage at room temperature, 8 high heat resistance, 9,10 and good mechanical properties 11 . Many studies have reported on the synthesis of propargyl ether resins, such as propargyl ether phenolic resin, 12,13 propargyl ether bisphenol A resin, 14–17 and propargyl ether phthalonitrile resin, 18–20 among others 21,22 .…”
Section: Introductionmentioning
confidence: 99%
“…Propargyl ether resin, a new type of high‐temperature‐resistant thermosetting resin developed in recent years, is a material with many potential advantages, including its good processability, long‐term storage at room temperature, 8 high heat resistance, 9,10 and good mechanical properties 11 . Many studies have reported on the synthesis of propargyl ether resins, such as propargyl ether phenolic resin, 12,13 propargyl ether bisphenol A resin, 14–17 and propargyl ether phthalonitrile resin, 18–20 among others 21,22 .…”
Section: Introductionmentioning
confidence: 99%
“…It has excellent bonding strength and weathering resistance (4). Many studies on the heat resistance of phenolic resin have been reported, including investigations of introduced silicon-boron heatresistant structures (5,6), benzoxazines (7,8) and phenolic cyanate esters (9,10); phenolic resins modified with allyl groups and double bonds (11,12); propargyl phenolic resins (13,14); and phthalonitrile-modified NV (15)(16)(17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%
“…[10]. There are many reports on the introduction of additional functional groups into propargyl resins aimed at reducing the curing exotherm or improving thermosets properties such as: phthalonitrile groups [11][12][13], azo-groups [14], benzoxazines [15,16], and epoxy groups [17]. In our previous work, it was shown that the introduction of additional allyl groups into the propargyl phenolic resin structure reduces the heat release during curing without degrading the properties of the resulting polymer matrix [18].…”
Section: Introductionmentioning
confidence: 99%